Enantioselective synthesis of (R)-2-cubylglycine including unprecedented rhodium mediated C–H insertion of cubane. Issue 5 (15th January 2019) - Houston, Sevan D.; Chalmers, Benjamin A.; Savage, G. Paul; Williams, Craig M.
Abstract : An enantioselective synthesis of the non-proteinogenic amino acid ( R )-2-cubylglycine and the first examples of cubane C–H insertion are reported. Abstract : The first enantioselective synthesis of ( R )-2-cubylglycine, an analogue of ( R )-2-phenylglycine in which the phenyl ring has been replaced by cubane, is disclosed. The key step was a telescoped Strecker reaction using ( S )-2-amino-2-phenylethanol as a chiral auxiliary. Exploration of an alternative synthetic approach resulted in unprecedented cubane C–H insertion.